Costs and benefits of isolation from siblings during family life in adult earwigs. (November 2022) - Van Meyel, Sophie; Meunier, Joël
Abstract : The benefits of parental care are often seen as a cornerstone of family life evolution. However, recent studies show that sibling interactions can also confer substantial benefits to juveniles. Here, we tested a new hypothesis suggesting that the need for juveniles to access sibling interactions may encourage juveniles to remain in a family group, thereby consolidating the early stages of family life evolution when parental care is facultative. We set up juveniles of the European earwig, Forficula auricularia (a family-living insect in which maternal care is facultative and juveniles can forage for themselves and cooperate with siblings) either alone, with siblings, or with siblings and their mother, and then quantified effects on the development, morphology and four fitness-related behaviours of the resulting adults. We found that isolated juveniles reached adulthood more quickly and that these adults were overall larger but showed impaired aggregation behaviour when compared with juveniles raised together with siblings or with siblings and their mother. By contrast, sibling deprivation did not affect offspring survival, male forceps length (an ornament involved in reproductive success) and three other behaviours in adults (boldness, general activity and exploration). All these results were independent of adult sex, although females overall reached adulthood earlier and were larger than males. Altogether, our findings suggest that the potential benefits of sibling interactions measured in this study play a minor role in the maintenance of earwig family life. They also emphasize the need to study the evolutionary drivers of family life in species where all members can switch from family to solitary life, a scenario that probably prevailed in the early evolution of sociality. Highlights: Do the benefits of sibling interactions support the maintenance of family life? We addressed this question by testing the effects of sibling deprivation in earwigs. We found that it produces adults with impaired aggregation and faster development. But it has no effect on survival and three other fitness-related behaviours. This questions the role of sibling interactions in the emergence of family life.